LncRNA np_5318 promotes renal ischemia-reperfusion injury through the TGF-β/Smad signaling pathway - Lu, Jing (Exp Ther Med, 2020)
Long noncoding (Lnc)RNA np_5318 has been proved to be involved in renal injury, while its functionality in renal ischemia-reperfusion (I/R) injury is unknown. Therefore, the present study aimed to investigate the role of lncRNA np_5318 in the development of renal I/R injury. Renal I/R injury model and I/R cell model were established in vitro. The expression of np_5318 in I/R cell was inhibited by small interfering (si)-np_5318 and increased by pc-np_5318. Renal function was detected and evaluated by automatic biochemical tests. Immunohistochemical staining was performed to detect the expression cluster of differentiation (CD)31, transforming growth factor (TGF)-β1 and (mothers against decapentaplegic homolog 3) Smad3 in renal tissue. The interaction between np_5318 and Smad3 was verified by chromatin immunoprecipitation (ChIP). Western blotting was performed to detect the expression levels of TGF-β1, Smad3 and phosphorylated (p)-Smad3 in renal tissue and renal cells. Expression of np_5318 in renal tissue and renal cells was detected by reverse transcription-quantitative PCR. Relative cell viability was confirmed by MTT assay. Renal function was impaired and pathological changes in renal tissue were observed in the renal I/R injury group, indicating the renal I/R injury model was successfully established. Compared with the sham group, the expression level of np_5318 significantly increased in the renal I/R injury group. ChIP data confirmed the interaction between np_5318 and Smad3. The expression of TGF-β1, Smad3 and p-Smad3 in renal tissue was also significantly increased in the renal I/R injury group. Furthermore, the I/R cell model in vitro was successfully constructed and np_5318 in I/R group was significantly increased compared with the control group. Cell growth was significantly suppressed in the I/R group compared with the control group. Additionally, transfection with pc-np_5318 significantly inhibited cell growth of I/R cells at 48 and 72 h. While inhibition of np_5318 by si-np_5318 significantly increased the cell growth of I/R cells at 48 and 72 h. Moreover, the level of TGF-β1, p-Smad3 and Smad3 was significantly increased in the I/R group compared with the control group, and transfection with pc-np_5318 significantly increased the level of TGF-β1, p-Smad3 and Smad3. While inhibition of np_5318 by si-np_5318 significantly suppressed the level of TGF-β1, p-Smad3 and Smad3. LncRNA np_5318 may participate in the development of renal I/R injury through TGF-β/Smad signaling pathway.